Las dos orillas de la ciencia. La traza pública e imperial de la ciencia española de Antonio Lafuente et al. - de Asúa, Miguel (Saber y Tiempo, 2015)
Antonio Lafuente et al. Madrid, Fundación Jorge Juan-Marcial Pons Historia, 2012